Extracellular Superoxide Dismutase, the Endothelial Basement Membrane, and the WNT Pathway: New Players in Vascular Normalization and Tumor Infiltration by T-Cells - Martínez-Rey, Diego; Carmona-Rodríguez, Lorena; Fernández-Aceñero, María Jesús; Mira, Emilia; Mañes, Santos (Frontiers in Immunology, 2020)
Tumor-infiltrating lymphocytes (TILs) are major players in the immune-mediated control of cancer and the response to immunotherapy. In primary cancers, however, TILs are commonly absent, suggesting T-cell entry into the tumor microenvironment (TME) to be selectively restricted. Blood and lymph vessels are the first barriers that circulating T-cells must cross to reach the tumor parenchyma. Certainly, the crossing of the endothelial cell (EC) basement membrane (EC-BM) - an extracellular matrix underlying EC - is a limiting step in T-cell diapedesis. This review highlights new data suggesting the antioxidant enzyme superoxide dismutase-3 (SOD3) to be a regulator of EC-BM composition in the tumor vasculature. In the EC, SOD3 induces vascular normalization and endows the EC-BM with the capacity for the extravasation of effector T-cells into the TME, which it achieves via the WNT signaling pathway. However, when activated in tumor cells, this same pathway is reported to exclude TILs. SOD3 also regulates TIL density in primary human colorectal cancers (CRC), thus affecting the relapse rate and patient survival.